Nicotine exposure during pregnancy programs osteopenia in male offspring rats via α4β2‐nAChR–p300‐ACE pathway. Issue 11 (7th September 2019) - Xiao, Hao; Wen, Yinxian; Pan, Zhengqi; Shangguan, Yangfan; Magdalou, Jacques; Wang, Hui; Chen, Liaobin
Abstract : Prenatal nicotine exposure (PNE) induces developmental toxicity in offspring. However, the long‐term harmful effects on bone development and the intrauterine programming mechanism attributed to PNE remain unclear. In the present research, pregnant Wistar rats were injected subcutaneously with nicotine (2 mg/kg/d) to obtain and analyze bone samples from the fetal and adult offspring. Bone marrow mesenchymal stem cells (BMSCs) were treated with nicotine during osteogenic differentiation to clarify the related molecular mechanisms. The results indicated that PNE led to bone dysplasia in the fetuses and reduced bone mass in the adult offspring, which was mediated by the sustained activation of the local bone renin angiotensin system (RAS) and suppressed osteogenic differentiation before and after birth. In vitro, nicotine suppressed BMSCs' osteogenic function through promoting angiotensin‐converting enzyme (ACE) expression and activating RAS. Furthermore, nicotine induced histone acetylase p300 into the nuclei of the BMSCs by acting on the α4β2‐nicotinic acetylcholine receptor (α4β2‐nAChR), leading to the increased histone 3 lysine 9 acetylation level of ACE and RAS activation. Taken together, the sustained activation of local bone RAS mediated prenatal nicotine‐induced osteopenia in adult offspring via the α4β2‐nAChR–p300‐ACE pathway.—Xiao, H., Wen, Y., Pan, Z., Shangguan, Y., Magdalou, J., Wang, H., Chen, L. Nicotine exposure during pregnancy programs osteopenia in male offspring rats via α4β2‐nAChR–p300‐ACE pathway. FASEB J. 33, 12972–12982 (2019). www.fasebj.org